Anxiety and Depression Symptoms in Athletes and Their Attitudes Towards These Problems - Bára Fanney Hálfdanardóttir 1988- (2016)
This study examined symptoms of general anxiety, sport performance anxiety and depression among 117 basketball players in the top league in Iceland. Furthermore, stigma towards anxiety and depression problems was explored. The Sport Anxiety Scale (SAS-2) was used to measure sport performance anxiety. The Hospital Anxiety and Depression Scale (HADS) was used to measure symptoms for general anxiety and depression. The Depression Stigma Scale was used to measure both personal and perceived stigma towards anxiety and depression. The results showed that measures of sport performance and general anxiety were strongly related (r=0.74) but not to the degree that they could be considered to be redundant of each other. There was a gender difference on SAS-2 and HADS anxiety subscale with female players scoring significantly higher than male players. There was no significant difference in scores between injured and non-injured players on the HADS anxiety and depression subscales. However, within the group of injured players, those who missed five or more practices scored significantly higher on the anxiety subscale. Players scored higher on measures of perceived stigma than personal stigma. The results suggest that when exploring levels of general anxiety in samples of athletes, it is important to take sport performance anxiety into account to avoid inflated estimates of symptom severity.